Thyroid ectopia: a case series - Sugunan, Aneesh; Hussain, Zahir S.; Palaniappan, Kumaran Muthappan; Puzhakkal, Shikhil; Ahmed, Althaf; Ramesh, Kalyanapu; Raghavan, Adarsh; Priya, Sahithi (International Surgery Journal, 2021)
Ectopic thyroid is a form of thyroid dysgenesis and is defined as the presence of thyroid tissue in an abnormal location. Its prevalence is about 1 per 1,00, 000-3,00,000 people, rising to 1 per 4,000-8,000 patients with thyroid diseases. The most common sites of ectopic thyroid are lingual (90%) and anterior neck (10%). They are usually diagnosed with hypothyroidism with a mass with, or without pressure symptoms in the 2nd or 3rd decade of life when there is increased demand of thyroid hormone. Presence of two ectopic foci of thyroid tissue simultaneously is rare, and very few such cases of dual thyroid ectopia have been reported. We present a case series of 3 ectopic thyroid with 3 different clinical presentation. The first case is a 19-year-old boy who presented with clinical and biochemical overt hypothyroidism and was discovered to have only a sublingual ectopic thyroid gland. The second case is a 16-year-old girl who presented with dysphagia and on evaluation was found to have a dual ectopic thyroid gland in the lingual and sub lingual region. The third case is a 28-year-old women who presented with a sub hyoid swelling which on evaluation was diagnosed as a dual ectopic thyroid in the lingual and sub lingual region.